A classification scheme of states and transitions for subantarctic ñire forest - Huertas Herrera, Alejandro; Peri, Pablo Luis; Soler Esteban, Rosina Matilde; Toro Manríquez, Mónica del Rosario; Lencinas, María Vanessa; Anderson, Christopher Brian; Pizarro, Cristobal; Cellini, Juan Manuel; Rosas, Yamina Micaela; Benitez, Julieta; Lorenzo, Cristian A.; Lopez, María Eugenia; et al.
State-transition models (S&TM) provide a powerful decision-analytic tool because they describe ecosystem dynamics in the context of landscape ecology, but also elucidate unwanted (sometimes irreversible) transition changes between states due to natural and human disturbances. The interest in this tool has increased in productive systems (e.g. forestry, silvopastoril) because it allows the identification of thresholds and therefore helps managers to decide the feasibility of implementing specific strategies. Nevertheless, in practice, it is not easy to structure the best S&TM because the many scenarios that can be defined at different spatial scales. The aim of this work is to provide consensus for the application of S&TM in Tierra del Fuego?s ñire (Nothofagus antarctica) forests at landscape level. We used disturbance intensity values (low, medium and high) of several drivers of forest change (DFC) to build a comprehensive classification diagram of possible scenarios. This diagram groups sets of S&TM that include ñire forests´ natural development phases (regeneration, initial and final optimal growth, and break down). Then, to define priority S&TM and DFC, we conducted discussions with stakeholders related to native forest management in southern Patagonia (scientists, decision makers, government, producers, technicians), and validated the proposal through participatory workshops and fieldwork to verify different situations (states). As a result, five main drivers of change were recognized by consensus: harvesting, livestock, fire, pathogens and wind-throw. This process also defined 10 states (e.g. open grassland with permanent weeds), 8 irreversible transitions and more than 20 possible combinations between developmental phases and DFC. Implementation of S&TM as an instrument for landscape planning would allow delineating the relationships between drivers of environmental change and native forest management. Furthermore, our work aims to establish this new paradigm as a way to produce a ...